Discursive Constructions of Domestic Corps-Based and International Social Outreach in The Salvation Army: Parallel Universes or an “Integrated Mission”?Research Article - Brooke, Petra Kjellen (Religion & development, 2025)
This article identifies a number of intersecting binaries that shape The Salvation Army’s (TSA) social outreach environment and examines efforts to unite these as part of an “integrated mission”. Two of these have been highlighted since the earliest days of TSA (i.e. social versus religious goals and reactive versus proactive approaches), while a third is more recent (i.e. domestic versus international outreach). Drawing on interviews with staff from two TSA territories – UK and Ireland, and Norway, Iceland and the Faroe Islands – we explore how a different language is used to describe domestic corps-based (church-based) social outreach compared to international social outreach and whether this goes beyond semantics and instead points to a variety in activities and outcomes or “parallel universes”. Our research demonstrates how some areas of TSA are questioning the binary between domestic and international social outreach not only because it leads to a lack of cross-fertilisation between different domains of activity that could lead to better outcomes, but also for its colonial underpinnings. Our findings suggest that as TSA develops its approach to “integrated mission”, the binary between domestic and international social outreach is more widely and critically examined, in addition to other binaries that have been debated for longer.